Global, regional, and national burden and trends of depressive disorders among women of childbearing age from 1990 to 2021: insights from GBD 2021 - Tang, Mingjie; Li, Yinghong; Shao, Jun; Li, Shiwei; Tang, Jiqin; Chen, Zhaoming (Frontiers in Psychology, 2025)
BackgroundDepressive disorders are highly prevalent and disabling mental illnesses among women of childbearing age (WCBA), especially with the surge in prevalence following the COVID-19 pandemic, but evidence on their burden remains insufficient. This study provides a thorough analysis of the burden of depressive disorders among WCBA at global, regional and national levels.MethodsThis study utilized data from Global burden of disease (GBD) 2021 to evaluate the trends in incidence, prevalence, Disability-Adjusted Life Years (DALYs) of depressive disorders among WCBA from 1990 to 2021. Data was stratified by time, age, region, and socio-demographic index (SDI). Moreover, this study utilized a range of analytical methods, including estimated annual percentage change (EAPC), Joinpoint regression, decomposition analysis and predictive modeling (Nordpred method).ResultsDepressive disorders in WCBA constitute a growing global health crisis, marked by a notable rise in absolute cases, accompanied by a slight downward age-standardized incidence rate (ASIR), age-standardized prevalence rate (ASPR), and age-standardized DALYs rate (ASDALYR). In 2021, there were 133.25 million incident cases, 121.24 million prevalent cases, and 21.04 million DALYs. In 2021, the global ASIR, ASPR, and ASDALYR were 6,808.01 (95% uncertainty interval [UI]: 5,049.99 to 9,106.66) per 100,000, 6173.45 (95% UI: 4,883.27 to 7,781.73) per 100,000, and 1,073.50 (95% UI: 686.73 to 1,562.48) per 100,000. High SDI region had the highest ASIR, ASPR, and ASDALYR. Furthermore, High-income North America exhibited the highest ASIR, ASPR and ASDALYR. Joinpoint regression analysis yielded a pronounced increase in ASIR subsequent to 2019. Nordpred predictive model demonstrated an upward trend in the ASIR, ASPR and ASDALYR of depressive disorders among WCBA by 2046.ConclusionDepressive disorders among WCBA show a globally rising burden, particularly in high SDI region, with a notable post-2019 increase. This underscores an urgent need for tailored public health action alleviate the growing mental health burden, particularly among WCBA.